Thallium-containing waste residue treatment method, thallium-containing waste residue geopolymer and application

The geological polymer containing thallium waste slag formed through polymerization solves the complexity and high cost problems of treating thallium waste slag in the prior art, realizes the stable fixation of thallium and the good mechanical properties of the material, and achieves the economic and environmental protection effects of harmless and resource-based treatment.

CN119569380APending Publication Date: 2025-03-07SHANXI CLEAN ENERGY RES INST OF TSINGHUA UNIV +1
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202411742481.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

When dealing with thallium-containing waste residue, the prior art has problems such as complex preparation process, harsh reaction conditions and high cost. The solid thallium effect is limited, and there is a risk of thallium migration and release.

Method used

By using thallium-containing waste residue as raw material, polymerization is carried out using alkaline reagents and oxidants to form thallium-containing waste residue geological polymers. By using physical wrapping, ion exchange and chemical adsorption, thallium elements are fixed in the three-dimensional network structure of the geological polymer.

Benefits of technology

It significantly reduces the migration and release risks of thallium in the environment, and the material has good mechanical properties, is suitable for environmentally friendly building materials or landfill materials, and realizes harmless and resource-based treatment of thallium-containing waste residue, with both economic and environmental benefits.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005162860770000081
    Figure BDA0005162860770000081
Patent Text Reader

Abstract

The invention relates to the technical field of heavy metal treatment, in particular to a thallium-containing waste residue treatment method, a thallium-containing waste residue geopolymer and application. The treatment method comprises the following steps: preparing a mixed solution containing an alkaline reagent and an oxidizing agent; adding thallium-containing waste residues and optional correction auxiliary materials into the mixed solution to obtain slurry; maintaining the slurry to obtain a thallium-containing waste residue geopolymer; wherein the correction auxiliary material comprises silicon dioxide and / or aluminum oxide. The thallium-containing waste residue geopolymer is obtained by taking the thallium-containing waste residue as a raw material through a polymerization reaction. The treatment method is excellent in thallium solidifying effect, and the obtained thallium-containing waste residue geopolymer is good in mechanical property and can be suitable for low-cost environment-friendly building materials or landfill materials serving as solid wastes, so that harmless and resourceful treatment of the thallium-containing waste residues is achieved, and the treatment method has economic and environment-friendly double benefits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heavy metal treatment, and in particular to a treatment method for thallium-containing waste slag, a thallium-containing waste slag geopolymer and an application thereof. Background Art

[0002] With the rapid development of industry, the accumulation and disposal of thallium-containing waste residues such as lithium slag, copper slag, and lead-zinc smelting slag have become increasingly prominent, and the resulting thallium pollution has brought severe environmental challenges to enterprises. As a highly toxic heavy metal element, thallium is far more toxic than common heavy metals such as Pb (lead), Hg (mercury), Cd (cadmium), Cu (copper), and Zn (zinc). It has strong accumulation, mutagenicity, and carcinogenic and teratogenic effects. Under the action of rainfall erosion and groundwater flow, the thallium element may penetrate into the soil, plants, and water sources of long-term storage of thallium-containing waste residues, and eventually accumulate in the human body through the food chain, causing acute or chronic thallium poisoning. At present, the main methods for treating thallium-containing waste residues are high-temperature incineration and curing agent addition, but these methods are complicated to operate and costly, and do not fundamentally eliminate the environmental risks of thallium pollution. For this reason, it is urgent to develop a treatment technology that can efficiently fix thallium from the source.

[0003] In the prior art, synthetic sulfur is subjected to hydrothermal reaction with thallium-containing waste residue to obtain treatment liquid and solid thallium treatment residue, which effectively reduces the risk of thallium leaching in the waste residue. However, the shelf life of synthetic sulfur is short, and the hydrothermal reaction conditions are harsh, which is not suitable for large-scale treatment of thallium-containing waste residue. Also, lithium mica waste residue, high calcium materials, high aluminum materials and functional auxiliary materials are mixed in proportion, ground, sintered, rapidly cooled, and ground twice to obtain a powder product. Under a high-temperature molten state, the silicate component and each component of the functional auxiliary material are combined with thallium to form an inert ceramic material, thereby preventing thallium from existing in an ionic state, and effectively solving the problem of thallium dissolution in lithium mica residue. However, the process is cumbersome, the roasting temperature is high, and the processing cost is high.

[0004] In summary, the current solidification methods for treating thallium-containing waste slag have problems such as complex preparation process, harsh reaction conditions, and high cost. It is urgent to develop a more efficient, economical and simple method for treating thallium-containing waste slag. Summary of the invention

[0005] The present invention aims to solve one of the technical problems in the related art to at least a certain extent. To this end, the present invention provides a method for treating thallium-containing waste residue, a thallium-containing waste residue geopolymer and its application. The method uses thallium-containing waste residue as a raw material to obtain a thallium-containing waste residue geopolymer through a polymerization reaction, and uses physical encapsulation, ion exchange and chemical adsorption to stably fix the thallium element in the three-dimensional network structure of the geopolymer, significantly reducing the mobility and release risk of thallium in the environment. In addition, the thallium-containing waste residue geopolymer has good mechanical properties and is suitable for low-cost environmentally friendly building materials or as a landfill material for solid waste, thereby realizing the harmless and resource-based treatment of thallium-containing waste residue, and having both economic and environmental benefits.

[0006] To this end, the first aspect of the present invention provides a method for treating thallium-containing waste slag, comprising:

[0007] preparing a mixed solution containing an alkaline reagent and an oxidant;

[0008] Adding thallium-containing waste residue and optional correction auxiliary materials into the mixed solution to obtain slurry;

[0009] Curing the slurry to obtain thallium-containing waste slag geopolymer;

[0010] Wherein, the correction auxiliary material includes silicon dioxide and / or aluminum oxide.

[0011] The present invention uses thallium-containing waste slag as a raw material to obtain thallium-containing waste slag geopolymer through polymerization reaction. The treatment method does not require high-temperature roasting or the addition of multiple auxiliary components such as flux, has fewer total treatment steps, and requires fewer types of raw materials. It has the advantages of simple process, excellent thallium solidification effect, and low treatment cost. One of silicon dioxide and aluminum oxide can be selected in the correction auxiliary material, that is, if the silicon-aluminum ratio in the slurry is increased, silicon dioxide can be appropriately added; if the silicon-aluminum ratio in the slurry is reduced, aluminum oxide can be appropriately added. Both can also be added at the same time or neither can be added if the slurry has reached the set silicon-aluminum ratio requirement.

[0012] According to an embodiment of the present invention, the alkaline agent includes silicate.

[0013] According to an embodiment of the present invention, the silicate includes at least one of sodium silicate, potassium silicate, lithium silicate and ammonium silicate.

[0014] According to an embodiment of the present invention, the alkaline reagent further includes at least one of sodium hydroxide, potassium hydroxide, calcium hydroxide, lithium hydroxide, sodium aluminate, and potassium aluminate.

[0015] According to an embodiment of the present invention, the modulus of the alkaline agent is 1-2.

[0016] According to an embodiment of the present invention, the oxidant includes at least one of potassium permanganate, sodium permanganate, calcium hypochlorite, ferric sulfate, hydrogen peroxide, and manganese dioxide.

[0017] According to an embodiment of the present invention, the mass ratio of the oxidant to the thallium-containing waste slag is 1:(10-30).

[0018] According to an embodiment of the present invention, the thallium-containing waste slag includes at least one of lithium slag, lead-zinc smelting waste slag, copper slag, fly ash, and slag.

[0019] According to an embodiment of the present invention, the particle size of the thallium-containing waste slag is 50-400 meshes.

[0020] According to an embodiment of the present invention, the molar ratio of silicon dioxide to aluminum oxide in the slurry is (1-4):1.

[0021] According to an embodiment of the present invention, the water-cement ratio of the slurry is 0.1-0.5.

[0022] According to an embodiment of the present invention, the mass ratio of the thallium-containing waste residue, the correction auxiliary material and the alkaline reagent is (55-90):(0-15):(5-30).

[0023] According to an embodiment of the present invention, the curing temperature is 30-70°C.

[0024] According to an embodiment of the present invention, the curing time is 5-48 hours.

[0025] The second aspect of the present invention provides a thallium-containing waste slag geopolymer obtained according to the treatment method described in the first aspect.

[0026] The thallium-containing waste slag geopolymer prepared by the invention has good thallium-fixing effect, significantly reduces the mobility and release risk of thallium in the environment, and has good mechanical properties.

[0027] The third aspect of the present invention provides the use of the thallium-containing waste slag geopolymer described in the second aspect or the thallium-containing waste slag geopolymer obtained according to the treatment method described in the first aspect in building materials.

[0028] The thallium-containing waste slag geopolymer obtained by the invention has good mechanical properties and is suitable for low-cost environmentally friendly building materials or as landfill materials for solid wastes, thereby achieving harmless and resourceful treatment of the thallium-containing waste slag, and having both economic and environmental benefits.

[0029] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. DETAILED DESCRIPTION

[0030] The embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0031] It should be noted that the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. Further, in the description of the present invention, unless otherwise specified, the meaning of "plurality" is two or more.

[0032] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0033] In order to make the present invention more easily understood, certain technical and scientific terms are specifically defined below. Unless otherwise clearly defined elsewhere in this document, all other technical and scientific terms used herein have the meanings commonly understood by those skilled in the art to which the present invention belongs.

[0034] In this document, the terms “include” or “comprising” are open expressions, that is, including the contents specified in the present invention but not excluding other contents.

[0035] As used herein, the terms "optionally", "optional" or "optionally" generally mean that the subsequently described event or circumstance may but need not occur, and that the description includes instances where the event or circumstance occurs and instances where it does not.

[0036] The existing treatment methods for thallium-containing waste slag often have complicated steps, and there are treatment steps with harsh conditions such as high-temperature roasting. In addition, the required raw materials are of various types and the treatment cost is high, which is not suitable for large-scale application. In addition, the existing treatment methods for thallium-containing waste slag have limited thallium-fixing effects, and the content of soluble thallium in the obtained products is still high, and thallium in other forms still exists in the powder products. When used as building materials, it is difficult to ensure the stable solidification of thallium due to frequent exposure to corrosive and harsh environments. There is a risk of thallium migration and release in the environment, which poses environmental and safety challenges.

[0037] According to an embodiment of the present invention, a first aspect of the present invention provides a method for treating thallium-containing waste slag, comprising:

[0038] (1) Prepare a mixed solution containing an alkaline reagent and an oxidizing agent.

[0039] The addition of alkaline reagents can make the system alkaline, and there are free OH - The oxidant can remove the Tl + Oxidized to Tl 3+ , and then with OH in the system - The hydroxyl complex ions with negative charge are formed, and the hydroxyl complex ions can produce hydrogen bonds with the surface hydroxyl groups of the geopolymer to be solidified. Thallium is wrapped and sealed in the thallium-containing waste slag geopolymer in the form of insoluble substances.

[0040] According to a specific embodiment of the present invention, the alkaline agent includes a silicate; the type of the silicate is not particularly limited, and as some specific examples, the silicate includes at least one of sodium silicate, potassium silicate, lithium silicate, and ammonium silicate.

[0041] According to a specific embodiment of the present invention, the alkaline reagent also includes at least one of sodium hydroxide, potassium hydroxide, calcium hydroxide, lithium hydroxide, sodium aluminate, and potassium aluminate.

[0042] According to a specific embodiment of the present invention, the modulus of the alkaline reagent is 1-2, and the modulus is the molar ratio of SiO2 to alkali metal oxide (such as Na2O, K2O, etc.) in the alkaline reagent. As some specific examples, the modulus of the alkaline reagent may be 1, 1.2, 1.4, 1.6, 1.8, 2, etc.

[0043] According to a specific embodiment of the present invention, the type of the oxidant is not particularly limited. As some specific examples, the oxidant includes but is not limited to at least one of potassium permanganate, sodium permanganate, calcium hypochlorite, ferric sulfate, hydrogen peroxide, and manganese dioxide.

[0044] According to a specific embodiment of the present invention, the preparation of the mixed solution can be specifically as follows: weigh appropriate amounts of alkaline reagent, oxidant and deionized water, mix them, stir until clear and transparent, and place them at room temperature to cool naturally to obtain the mixed solution.

[0045] (2) adding thallium-containing waste residue and optional correction auxiliary materials to the mixed solution to obtain a slurry;

[0046] Wherein, the correction auxiliary material includes silicon dioxide and / or aluminum oxide.

[0047] The silicon dioxide and aluminum oxide in the correction auxiliary materials are important raw materials for participating in the polymerization reaction to form geopolymers. The free thallium ions can exchange ions with the metal ions in the geopolymers containing thallium waste residues, and are used to balance the negative charge of the aluminum oxide tetrahedron and are bonded and fixed in the three-dimensional network structure of the geopolymer. At the same time, the obtained geopolymer has a dense network structure, which significantly enhances the interaction with thallium in different occurrence forms and effectively inhibits the migration and leaching of thallium.

[0048] According to a specific embodiment of the present invention, the mass ratio of the oxidant to the thallium-containing waste slag is 1:(10-30). As some specific examples, the mass ratio of the oxidant to the thallium-containing waste slag may be 1:10, 1:15, 1:20, 1:25, 1:30, etc.

[0049] According to a specific embodiment of the present invention, the type of the thallium-containing waste slag is not particularly limited, and it can be any industrial by-product waste slag containing thallium. As some specific examples, the thallium-containing waste slag includes but is not limited to at least one of lithium slag, lead-zinc smelting waste slag, copper slag, fly ash, and slag.

[0050] According to a specific embodiment of the present invention, the particle size of the thallium-containing waste slag is 50-400 mesh. As some specific examples, the particle size of the thallium-containing waste slag can be 50 mesh, 100 mesh, 200 mesh, 300 mesh, 400 mesh, etc.

[0051] According to a specific embodiment of the present invention, the molar ratio of silica to alumina in the slurry is (1-4):1. As some specific examples, the molar ratio of silica to alumina in the slurry may be 1:1, 2:1, 3:1, 4:1, etc.

[0052] According to a specific embodiment of the present invention, the water-cement ratio of the slurry is 0.1-0.5. As some specific examples, the water-cement ratio of the slurry may be 0.1, 0.2, 0.3, 0.4, 0.5, etc. The water-cement ratio is the ratio of the mass of water in the mixture of alkaline reagent and oxidant to the mass of the mixture of thallium-containing waste slag and correction auxiliary materials, that is, the liquid-to-solid ratio.

[0053] According to a specific embodiment of the present invention, the mass ratio of the thallium-containing waste residue, the correction auxiliary material and the alkaline reagent is (55-90):(0-15):(5-30). As some specific examples, the mass ratio of the thallium-containing waste residue, the correction auxiliary material and the alkaline reagent can be 55:0:5, 65:5:10, 75:10:20, 90:15:30, etc.

[0054] According to a specific embodiment of the present invention, the purity of silica and alumina in the correction auxiliary material is independently 90%-100%. As some specific examples, the purity of silica and alumina in the correction auxiliary material may be 90%, 92%, 94%, 96%, 98%, 100%, etc.

[0055] According to a specific embodiment of the present invention, the specific operation of preparing the slurry is to crush and grind the thallium-containing waste residue and the correction auxiliary material, weigh the thallium-containing waste residue and the correction auxiliary material in proportion, add the cooled mixed liquid and stir to obtain the slurry.

[0056] (3) curing the slurry to obtain thallium-containing waste slag geopolymer.

[0057] By controlling the curing temperature and curing time, the progress of the polymerization reaction can be regulated to obtain the thallium-containing waste slag geopolymer.

[0058] According to a specific embodiment of the present invention, the curing temperature is 30-70°C. As some specific examples, the curing temperature may be 30°C, 40°C, 50°C, 60°C, 70°C, etc.

[0059] According to a specific embodiment of the present invention, the curing time is 5-48 hours. As some specific examples, the curing time may be 5 hours, 15 hours, 26 hours, 37 hours, 48 ​​hours, etc.

[0060] According to a specific embodiment of the present invention, the specific operation of preparing the thallium-containing waste slag geopolymer is to pour the slurry into the mold three times, mechanically vibrate for 1 to 5 minutes to achieve uniform distribution, and discharge excess bubbles, scrape the film and transfer it to an incubator for curing and forming, and then demold to obtain the thallium-containing waste slag geopolymer.

[0061] According to an embodiment of the present invention, a second aspect of the present invention provides a thallium-containing waste slag geopolymer obtained according to the treatment method described in the first aspect.

[0062] The thallium-containing waste slag geopolymer prepared by the invention has good thallium-fixing effect and also has good mechanical properties.

[0063] According to an embodiment of the present invention, the third aspect of the present invention provides the use of the thallium-containing waste slag geopolymer described in the second aspect or the thallium-containing waste slag geopolymer obtained according to the treatment method described in the first aspect in building materials.

[0064] The invention obtains thallium-containing waste slag geopolymer through polymerization reaction. The dense network structure of the geopolymer not only effectively inhibits the migration and leaching of thallium, but also is conducive to the improvement of strength, so that the thallium-containing waste slag geopolymer has good mechanical strength, can be used as medium-low strength green building materials or for solid waste landfill, realizes the harmless, resource-based and reduced disposal of thallium-containing waste slag, and thus has the dual benefits of economy and environmental protection.

[0065] The scheme of the present invention will be explained below in conjunction with the embodiments. It will be appreciated by those skilled in the art that the following embodiments are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Where specific techniques or conditions are not indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used are not indicated by the manufacturer and are all conventional products that can be obtained commercially.

[0066] Example 1

[0067] Weigh 3.14 g of sodium hydroxide, 30.00 g of sodium silicate, 7.69 g of potassium permanganate and 82 g of deionized water, mix them so that the modulus is 1.4, stir until clear and transparent, and leave them to cool naturally at room temperature to obtain a mixed solution;

[0068] The lithium slag and the correction auxiliary material were crushed and ground, and 200 g of lithium slag and 5 g of the correction auxiliary material (including 2.88 g of silicon dioxide and 2.12 g of aluminum oxide) were weighed, wherein the particle size of the lithium slag was 200 mesh, so that the molar ratio of silicon dioxide to aluminum oxide in the system was 3:1, and the water-cement ratio was 0.4, and the cooled mixed solution was added and stirred to obtain a slurry;

[0069] The slurry was poured into the mold three times, mechanically vibrated for 2 minutes to achieve uniform distribution and expel excess bubbles, the film was scraped flat and transferred to an incubator, cured at 50°C for 24 hours, and then demolded to obtain the thallium-containing waste slag geopolymer.

[0070] The compressive strength of the thallium-containing waste slag geopolymer prepared according to the above process and the thallium content in the leaching solution detected by ICP-MS are shown in Table 1.

[0071] Example 2

[0072] Weigh 7.99 g of potassium hydroxide, 4.48 g of calcium hydroxide, 36 g of potassium silicate, 7.69 g of ferric sulfate and 63 g of deionized water, mix them so that the modulus is 1.2, stir until clear and transparent, and place them at room temperature to cool naturally to obtain a mixed solution;

[0073] The lithium slag, the lead-zinc smelting waste slag, and the correction auxiliary materials were crushed and ground, and 120 g of lithium slag, 80 g of lead-zinc smelting waste slag, and 10 g of correction auxiliary materials (including 5.75 g of silicon dioxide and 4.25 g of aluminum oxide) were weighed, wherein the particle size of the lithium slag and the lead-zinc smelting waste slag was 150 mesh, so that the molar ratio of silicon dioxide to aluminum oxide in the system was 2.5:1, and the water-cement ratio was 0.3, and the cooled mixed solution was added and stirred to obtain a slurry;

[0074] The slurry was poured into the mold three times, mechanically vibrated for 5 minutes to achieve uniform distribution and expel excess bubbles, the film was scraped flat and transferred to an incubator, cured at 70°C for 12 hours, and then demolded to obtain the thallium-containing waste slag geopolymer.

[0075] The compressive strength of the thallium-containing waste slag geopolymer prepared according to the above process and the thallium content in the leaching solution detected by ICP-MS are shown in Table 1.

[0076] Comparative Example 1

[0077] Weigh 5.02 g of sodium hydroxide, 15.00 g of sodium silicate, 5.86 g of potassium permanganate and 82 g of deionized water, mix them so that the modulus is 0.8, stir until clear and transparent, and leave them to cool naturally at room temperature to obtain a mixed solution;

[0078] The lithium slag and the correction auxiliary material were crushed and ground, and 195 g of lithium slag and 10 g of the correction auxiliary material (including 8.48 g of silicon dioxide and 1.52 g of aluminum oxide) were weighed, wherein the particle size of the lithium slag was 200 mesh, so that the molar ratio of silicon dioxide to aluminum oxide in the system was 5:1, and the water-cement ratio was 0.3, and the cooled mixed solution was added and stirred to obtain a slurry;

[0079] The slurry was poured into the mold three times, mechanically vibrated for 2 minutes to achieve uniform distribution and expel excess bubbles, the film was scraped flat and transferred to an incubator, cured at 50°C for 24 hours, and then demolded to obtain the thallium-containing waste slag geopolymer.

[0080] The compressive strength of the thallium-containing waste slag geopolymer prepared according to the above process and the thallium content in the leaching solution detected by ICP-MS are shown in Table 1.

[0081] Comparative Example 2

[0082] Weigh 3.08 g of potassium hydroxide, 1.43 g of calcium hydroxide, 17 g of potassium silicate, 5.08 g of ferric sulfate and 60 g of deionized water, mix them so that the modulus is 2.2, stir until clear and transparent, and place them at room temperature to cool naturally to obtain a mixed solution;

[0083] The lithium slag, the lead-zinc smelting waste slag, and the correction auxiliary material were crushed and ground, and 85g of lithium slag, 115g of lead-zinc smelting waste slag, and 10g of correction auxiliary material (including 8.35g of silicon dioxide and 1.65g of aluminum oxide) were weighed, wherein the particle size of the lithium slag and the lead-zinc smelting waste slag was 150 mesh, so that the molar ratio of silicon dioxide to aluminum oxide in the system was 4.5:1, and the water-cement ratio was 0.3, and the cooled mixed solution was added and stirred to obtain a slurry;

[0084] The slurry was poured into the mold three times, mechanically vibrated for 5 minutes to achieve uniform distribution and expel excess bubbles, the film was scraped flat and transferred to an incubator, cured at 70°C for 12 hours, and then demolded to obtain the thallium-containing waste slag geopolymer.

[0085] The compressive strength of the thallium-containing waste slag geopolymer prepared according to the above process and the thallium content in the leaching solution detected by ICP-MS are shown in Table 1.

[0086] Test Case

[0087] The thallium-fixing effect and compressive strength test of the thallium-containing waste slag geopolymer prepared in the examples and comparative examples were tested, and the test method was as follows:

[0088] (1) Test on the effect of geopolymer in fixing thallium in waste residue containing thallium:

[0089] The thallium-containing waste geopolymer specimens cured for 28 days were subjected to leaching tests using sulfuric acid and nitric acid method, and the thallium content in the leaching solution was detected using ICP-MS.

[0090] (2) Compressive strength test of geopolymer containing thallium waste residue:

[0091] The compressive strength of thallium-containing waste slag geopolymer cured for 7d and 28d was tested by a press.

[0092] Table 1

[0093]

[0094] According to the data in Table 1, the thallium content in the leachate of Example 1-2 is significantly lower than that of Comparative Example 1-2, and the compressive strength is significantly higher than that of Comparative Example 1-2, indicating that the thallium-containing waste slag geopolymer obtained according to the preparation method of the present invention has excellent thallium-fixing effect and mechanical properties, can realize the harmless and resourceful treatment of thallium-containing waste slag, and has both economic and environmental benefits.

[0095] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.

[0096] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for treating thallium-containing waste residue, characterized in that: include: preparing a mixed solution containing an alkaline reagent and an oxidant; Adding thallium-containing waste residue and optional correction auxiliary materials into the mixed solution to obtain slurry; Curing the slurry to obtain thallium-containing waste slag geopolymer; Wherein, the correction auxiliary material includes silicon dioxide and / or aluminum oxide.

2. The processing method according to claim 1, characterized in that: The alkaline agent includes a silicate; Optionally, the silicate includes at least one of sodium silicate, potassium silicate, lithium silicate, and ammonium silicate; Optionally, the alkaline reagent further comprises at least one of sodium hydroxide, potassium hydroxide, calcium hydroxide, lithium hydroxide, sodium metaaluminate, and potassium metaaluminate; Optionally, the alkaline agent has a modulus of 1-2.

3. The processing method according to claim 1, characterized in that: The oxidant includes at least one of potassium permanganate, sodium permanganate, calcium hypochlorite, ferric sulfate, hydrogen peroxide, and manganese dioxide.

4. The processing method according to claim 1, characterized in that: The mass ratio of the oxidant to the thallium-containing waste slag is 1:(10-30).

5. The processing method according to claim 1, characterized in that: The thallium-containing waste residue includes at least one of lithium slag, lead-zinc smelting waste residue, copper slag, fly ash, and slag; Optionally, the particle size of the thallium-containing waste residue is 50-400 mesh.

6. The processing method according to claim 1, characterized in that: The molar ratio of silicon dioxide to aluminum oxide in the slurry is (1-4):1; Optionally, the water-cement ratio of the slurry is 0.1-0.

5.

7. The processing method according to claim 1, characterized in that: The mass ratio of the thallium-containing waste residue, the correction auxiliary material and the alkaline reagent is (55-90):(0-15):(5-30).

8. The processing method according to claim 1, characterized in that: The curing temperature is 30-70°C; Optionally, the curing time is 5-48h.

9. A thallium-containing waste slag geopolymer, characterized in that: The thallium-containing waste slag geopolymer is obtained by the treatment method described in any one of claims 1-8.

10. Use of the thallium-containing waste slag geopolymer obtained by the treatment method according to any one of claims 1 to 8 or the thallium-containing waste slag geopolymer according to claim 9 in building materials.

Citation Information

Cited By

  • Cooperative treatment method for beryllium and thallium-containing waste residues

    CN120885532A

  • A method for synergistic treatment of beryllium and thallium-containing waste residues

    CN120885532B